Magnetic Clouds Seen at Different Locations in the Heliosphere - Rodriguez, L. (2008)
We analyze two magnetic clouds (MCs) observed in different points of the heliosphere. The main aim of the present study is to provide a link between the different aspects of this phenomenon, starting with information on the origins of the MCs at the Sun and following by the analysis of in-situ observations at 1 AU and at Ulysses. The candidate source regions were identified in SOHO/EIT and SOHO/MDI observations. They were correlated with H-α images that were obtained from ground-based observatories. Hints on the internal magnetic field configuration of the associated coronal mass ejections are obtained from LASCO C2 images. In interplanetary space, magnetic and plasma moments of the distribution function of plasma species (ACE/Ulysses) were analyzed together with information on the plasma composition, and the results were compared between both spacecraft in order to understand how these structures interact and evolve in their cruise from the Sun to 5 AU. Additionally, estimates of global magnitudes of magnetic fluxes and helicity were obtained from magnetic field models applied to the data in interplanetary space. We have found that these magnetic characteristics were well kept from their solar source, up to 5 AU where Ulysses provided valuable information which, together with that obtained from ACE, can help to reinforce the correct matching of solar events and their interplanetary counterparts.